KARAKTERISASI DAN UJI-PENGOLAHAN (TREATABILITY TEST) AIR LIMBAH TEKSTIL INTI SARI SECARA BIOLOGI - Milono Poesponegoro (Research Center for Chemistry - LIPI, 1997)
Characterization and treatability test of textile wastewater using biological process were studied. Samples of the wastewater were obtainedfrom a local blue-jeans textile industry in Bandung. Results of chemical analysis indicated that beside the textile wastewater showed a high pH value, it contained chemical pollutant in high concentrations. It was found that the textile wastewater of blue jeans has a pH value of 12.6, deep blue coloured with optical density of 0.80 - 0.88; high in solid concentrations with the concentration of soluble solids, suspended solids and ash content of respectively 4526 - 4897 mg/l, 2205 - 2412mg/l, and 2704 - 3074 mg/l; COD of 376 - 1538 mg/l and BOD5 of 143 - 575 mg/l. The ratio of BOD5/COD was about 0.32 - 0.45 with an average value of 0.38.The concentration of organic materials varied widely from sample to .sample, with a value of the BOD5/COD ratio of less than 50%. Tretability test of textile wastewater using shake-flask technique showed that the textile wastewater could be treated successfully by aerobic biological process when a proper balance of nutrients and suitable organisms were available. Chemical flocculation pre-trentment was found to lower the rate of biological degradation of organic materials contained in the textile wastewater. It was found that after 3 days of incubation, the mean rate of organic degradation reached 174 mg/l/day for the textile wastewater which received no flocculation pretreatment with alum, and only 10 mg/l/day for that which received flocculation pre-treatment with alum. The addition of nutrient (nitrogen and phosphorous) to the textile wastewater without flocculation pre-treatment increased the mean rate of organic degradation from 174 mg/l/day to 240 mg/l/day after 3 days of incubation. It was also found the nutrient addition and bacterial inoculum to the textile wastewater without flocculation pre-treatment increased the mean rate of organic degradation from 174 mg/l/day to 247 mg/l/day, after 3 days of incubation.Treatability test of textile wastewater by a contlnouous culture technique using perforated-plate column showed that the COD of effluent was constantly dropped and achieved a stationary condition after 50 hours of the continous process, and at the stationary phase the continuous process produced effluent with COD values of less than 100 mg/l. Continuous process with a hydraulic retention time (0) of 2.0 day produced effluent with a COD value of 77 mgll. Reducing the hydraulic retention time did not much affect the COD value of the effluent, i.e 72 mgfl for 0 = 1.0 day, and 56 mgll for 0 = 0.5 day. This could probably due to the achievement of the maximum efficiency of treatment, t.e. about 71% for the hydraulic retention time of 0.5 - 2.0 day.